2009
DOI: 10.1063/1.3140609
|View full text |Cite
|
Sign up to set email alerts
|

Tunable light trapping for solar cells using localized surface plasmons

Abstract: Effective light management is imperative in maintaining high efficiencies as photovoltaic devices become thinner. We demonstrate a simple and effective method of enhancing light trapping in solar cells with thin absorber layers by tuning localized surface plasmons in arrays of Ag nanoparticles. By redshifting the surface plasmon resonances by up to 200 nm, through the modification of the local dielectric environment of the particles, we can increase the optical absorption in an underlying Si wafer fivefold at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
322
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(339 citation statements)
references
References 10 publications
14
322
1
2
Order By: Relevance
“…This disadvantage generally exists for any sub-wavelength light trapping mechanism and it has to be overcome [7,32] . Based on these design principles, numerous computational and experimental studies have been reported on tuning the metal material, the shape, size and packing density, the dielectric environment and the position of the plasmonic nanostructures in PV devices to achieve enhanced light absorption for various types of solar cells [10,13,15,24,[31][32][33][34][35][36][37][38] .…”
Section: Guidance Direction Of Lightmentioning
confidence: 99%
“…This disadvantage generally exists for any sub-wavelength light trapping mechanism and it has to be overcome [7,32] . Based on these design principles, numerous computational and experimental studies have been reported on tuning the metal material, the shape, size and packing density, the dielectric environment and the position of the plasmonic nanostructures in PV devices to achieve enhanced light absorption for various types of solar cells [10,13,15,24,[31][32][33][34][35][36][37][38] .…”
Section: Guidance Direction Of Lightmentioning
confidence: 99%
“…By using relatively large Ag islands (around 50 nm) the scattering of light into the PV cell is enhanced, the plasmon resonance of these particles can be tuned so it is around the desired wavelength by modifying the surrounding local dielectric environment [179]. Note that the enhancement may be optimised by varying the shape, size, material and surface coverage of the nanostructure [178][179][180][181][182][183][184]. Figure 6a shows that higher aspect nanostructures (i.e., cylinders rather than spheres) maximises the fraction of incident light scattered into the photoactive layer and hence enhances the solar cell efficiency [180].…”
Section: Existing and Emerging Applicationsmentioning
confidence: 99%
“…Recall Section 3, in particular equations (16) and (17) which showed that scattering dominates in larger particles whereas absorbance is more important for smaller particles. By using relatively large Ag islands (around 50 nm) the scattering of light into the PV cell is enhanced, the plasmon resonance of these particles can be tuned so it is around the desired wavelength by modifying the surrounding local dielectric environment [179]. Note that the enhancement may be optimised by varying the shape, size, material and surface coverage of the nanostructure [178][179][180][181][182][183][184].…”
Section: Existing and Emerging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, nanotechnology has been used with plasmonic light trapping of metal nanoparticles (NP) like gold (Au) or silver (Ag) [3][4][5]. For incorporating metal NPs into solar cells, different methods have been established that includes island annealing and colloidal metal particles [6][7]. Also, some numerical models have been developed to understand the plasmonic effect [8].…”
Section: Introductionmentioning
confidence: 99%